1994
DOI: 10.1111/j.1399-302x.1994.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress response of Porphyromonas gingivalis

Abstract: The heat shock response of Porphyromonas gingivalis was examined by 1- and 2-dimensional polyacrylamide gel electrophoresis after metabolic labeling with [14C]-amino acids. When P. gingivalis cells were shifted from 37 degrees C to 42 degrees C, elevated synthesis of 4 proteins with the apparent molecular weight of 92, 80, 74, and 62 kDa was observed, and synthesis of a 50-kDa protein decreased during heat shock. The 74- and 62-kDa proteins were identified as homologs of Escherichia coli DnaK and GroEL respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 42 publications
3
48
0
Order By: Relevance
“…Previous studies have shown that expression of dnaK and groEL was increased when P. gingivalis was stressed at 42°C, but expression of these genes did not change in response to oxidative stress or pH (32). These data suggest that dnaK and groEL are related to temperature stress, but not oxidative or pH stress.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown that expression of dnaK and groEL was increased when P. gingivalis was stressed at 42°C, but expression of these genes did not change in response to oxidative stress or pH (32). These data suggest that dnaK and groEL are related to temperature stress, but not oxidative or pH stress.…”
Section: Discussionsupporting
confidence: 52%
“…There have been studies which reported (i) detection of common stress proteins in oral microorganisms (7)(8)(9), (ii) cloning of these stress proteins (10,24,43), (iii) demonstration of potent induction of bone resorption (16,30), or (iv) purification of specific heat shock proteins from various Hsp families (4,10,14,20,23,39,40,44). There have been several studies that reported an association between periodontal disease and titers of antibody to Hsp65 and Hsp90 in serum (17,22,24,31).…”
mentioning
confidence: 99%
“…Polyclonal antibodies raised against A. actinomycetemcomitans GroEL react strongly with E. coli GroEL and, to a lesser extent, with P. gingivalis and B. forsythus GroELs (Hinode et al, 1998a). The heat-shock response of P. gingivalis was first examined by Lu and McBride (1994) using one-and two-dimensional SDS-PAGE after labeling the cells with 14 Camino acids. Four proteins were up-regulated (62, 74, 80, and 92 kDa), and one (50 kDa) was down-regulated following a heat stress (Lu and McBride, 1994).…”
Section: (31) Groes and Groel Proteinsmentioning
confidence: 99%
“…The heat-shock response of P. gingivalis was first examined by Lu and McBride (1994) using one-and two-dimensional SDS-PAGE after labeling the cells with 14 Camino acids. Four proteins were up-regulated (62, 74, 80, and 92 kDa), and one (50 kDa) was down-regulated following a heat stress (Lu and McBride, 1994). Western immunoblotting analysis was used to confirm that P. gingivalis can increase production of GroEL and DnaK when subjected to a temperature shift from 35°C to 43°C (Vayssier et al, 1994).…”
Section: (31) Groes and Groel Proteinsmentioning
confidence: 99%